TREND OF HALAL TOURISM AS A LIVING QUR'AN PRACTICE IN LOMBOK - Maryam, Siti (STAI Darul Kamal NW Kembang Kerang, 2020)
The trend of halal tourism is not only seen as an effort to develop the economy of an area, but also the concept of making Muslim tourists comfortable when carrying out tourism activities, by providing adequate worship facilities, water availability, halal food in restaurant and hotel, prevention of practice immoral and others. This atricle wil focus on: (1) how the concept of halal tourism; (2) what factors cause halal tourism to be developed; (3) how halal tourism affects religiosity and increases the economic welfare of the region. This research found that the concept of halal tourism is very important to continue to be developed, because it is a practice of reviving the Qur'an (living Qur'an) in tourism activities. In addition, halal tourism is also a manifestation of hifz din (safeguarding religion), by doing so that religious rules are implemented properly and correctly